INFLUENCE OF LEADERSHIP STYLE AND COMMUNICATION SKILLS ON CAREER ADVANCEMENT: THE ROLE OF STAFF PERFORMANCE AS AN INTERVENING FACTOR IN RADIOLOGY INSTALATION OF SOUTH TANGERANG CITY GENERAL HOSPITAL - Shirley Eleonora Gusmariny Teterissa; Cicilia Widyaningsih; Supardjo Supardjo (Multidisciplinary Research Studies in Social Sciences, 2026)
This study aims to analyze the influence of leadership style and communication skills on career path with staff performance as an intervening variable at the Radiology Department of South Tangerang City General Hospital (RSU Kota Tangerang Selatan). The background of this research is based on the need for effective human resource management in hospitals to improve staff performance and career development. This study uses a quantitative approach with a cross-sectional design and path analysis, involving all medical and non-medical staff as respondents, using a total sampling technique. The results show that leadership style and communication skills significantly influence staff performance and career path. Furthermore, staff performance is proven to be an intervening variable that strengthens the relationship between leadership style and communication skills on career path. These findings have practical implications for hospital management in making strategic decisions related to career development and performance improvement through adaptive leadership styles and effective organizational communication.Keywords: Leadership Style, Communication Skills, Staff Performance, Career Path, Radiology Department, Hospital.